2021
DOI: 10.1016/j.vetmic.2021.109067
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of caprine airway epithelial cells grown in an air-liquid interface system to study caprine respiratory viruses and bacteria

Abstract: Respiratory diseases negatively impact the global goat industry, but are understudied. There is a shortage of established and biological relevant in vitro or ex vivo assays to study caprine respiratory infections. Here, we describe the establishment of an in vitro system based on well-differentiated caprine airway epithelial cell (AEC) cultures grown under air liquid interface conditions as an experimental platform to study caprine respiratory pathogens. The functional differentiation of the AEC cultures was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Compared with ICV, IDV has broad cell tropism owing to its increased binding avidity towards diverse glycans and can grow not only in continuous cell lines, but also in most of the primary cells from bovine [162], caprine [163], equine, and porcine species [164]. A comparison of in vitro cellular tropism of the IDV to ICV, determined by RT-PCR in cell lines of different species origins, such as swine testicle (ST) cells [165], (MDCK), green African monkey kidney cells (Marc-145), human rectal tumor (HRT-18G), baby hamster kidney (BHK-21), and porcine kidney (PK-15) cells, showed that IDV replicated to appreciable titers in all, with minimal replication in BHK-21 and PK-15 cells [82].…”
Section: Broad Cell and Tissue Tropism Of Idv Over Icvmentioning
confidence: 99%
“…Compared with ICV, IDV has broad cell tropism owing to its increased binding avidity towards diverse glycans and can grow not only in continuous cell lines, but also in most of the primary cells from bovine [162], caprine [163], equine, and porcine species [164]. A comparison of in vitro cellular tropism of the IDV to ICV, determined by RT-PCR in cell lines of different species origins, such as swine testicle (ST) cells [165], (MDCK), green African monkey kidney cells (Marc-145), human rectal tumor (HRT-18G), baby hamster kidney (BHK-21), and porcine kidney (PK-15) cells, showed that IDV replicated to appreciable titers in all, with minimal replication in BHK-21 and PK-15 cells [82].…”
Section: Broad Cell and Tissue Tropism Of Idv Over Icvmentioning
confidence: 99%
“…Current methods to determine virulence potential and host-pathogen interactions of mycoplasmas have relied on (i) in vivo experimental infections of the natural or alternative hosts [32][33][34][35] or on (ii) in vitro infections [21,[36][37][38][39][40]. Infections of the natural host, especially for reptiles, can be challenging but have been successfully used to confirm that both M. alligatoris [27,41] and M. agassizii [42,43] are etiologic agents of disease in alligators and tortoises, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assays have focused on the use of cell lines to screen a large number of Mycoplasma spp. for pathogenic potential and to understand cellular and molecular interactions [10,21,36,37,39,40,44]. However, cell lines lack a functioning immune system which is a key component of mycoplasmal disease [1,2,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%